Doing Research that is Useful to Practice a Model and Empirical Exploration - Mohrman, Susan Albers; Gibson, Cristina B.; Mohrman, Allan M. (Academy of Management Journal, 2001)
Drawing from literature on knowledge transfer and cognition, we develop a theoretical model for conducting research that is useful to practitioners. We explore the potential of this model by examining the usefulness of a research project involving ten companies. Perceived usefulness is related to the extent that members' organization self-design activities are informed by research results and to the existence of forums where researchers and practitioners jointly interpret results. We discuss implications for organizational science.